Mechanical and chemical weeding effects on the weed structure in durum wheat - Wozniak, Andrzej (Italian Journal of Agronomy, 2020)
A three-year field experiment was performed to study weed infestation of durum wheat at the stage of emergence and full maturity. Two weeding systems (WS) were used in the post-harvest period: i) mechanical weeding (MW); and ii) chemical weeding (CW). In the MW system, soil underwent shallow ploughing at a depth of 10-12 cm and double harrowing (after ploughing and 3 weeks later), whereas glyphosate only was used in the CW system. In the springtime, in both MW and CW systems, a tillage set consisting in a cultivator, a string roller and harrowing was used. Overall, the number of weeds m2, the number of weed species and the value of weed diversity indices were always higher in MW than in the CW systems in each study year at both the emergence and full maturity stage of durum wheat. The study demonstrated that at the stage of durum wheat emergence, more weeds per m2 occurred in the MW than in the CW system in each study year. Moreover, the MW systems was characterized by a higher number of weed species as well as by a higher value of weed diversity index compared to the CW system.